Síndrome Burnout relacionado con la inteligencia emocional en los empleados del Centro de Salud tipo C del cantón Tosagua, periodo diciembre-2020 junio-2021 - Domínguez Marcillo, Juan Carlos (2023)
The present research work points out the process and cause of the Burnout Syndrome that is closely linked to emotional intelligence in the exercise of the functions of those who work in the Type C Health Center in Tosagua, considering that professional burnout is continuous in people who they assume actions, that is, a state that associates stress with the results of work activities. For this, the research methods were taken as tools, which helped in the elaboration of hypotheses and conclusions; after that, the research techniques allowed the collection of information through the interview and the survey and the types of research helped in the development of the inquiry. The results obtained from this work were a comparison of theory with practice in the Health Center under study, in addition to the survey confirming that this syndrome existed within the Type C Health Center in Tosagua on 29 % of your employees, hence most of the workers felt exhausted because they never find enough vitality in all tasks. In addition, the lack of attention in the improvement of the tasks or importance towards the users, is relevant, despite the presence of the syndrome, since it avoids reaching the desired goals and with the level of demands within the work activities.